Industrialized synthetic method of vismodegib - LI ZICHENG; LU JIE; LIU PENG; DUAN LANG; ZHANG WEIQUN; JIN LEI (2015)
The invention discloses an industrialized synthetic method of vismodegib. The method comprises the following steps: a, conducting a halogenated reaction on p-chloronitrobenzene and a halogen reagent strong inorganic acid by using an inorganic strong acid as a solvent to obtain an intermediate 2; b, reducing the nitro in the intermediate 2 by a reduction agent into a into amino in a water-soluble organic solvent to obtain an intermediate 3; c, protecting the amino in the intermediate 3 to obtain an intermediate 4; d, reacting the intermediate 4 with bis(pinacolato)diboron and 2-bromo pyridine to obtain an intermediate 5; e, reacting the intermediate 5 with an alcohol solution of halogen hydride at room temperature to obtain an intermediate 6; and f, reacting the intermediate 6 with 2-chloro-4-methylsulfonyl benzoyl chloride to obtain vismodegib. The invention adopts cheap starting materials, has the advantages of simple operation, small amount of palladium catalyst, high yield of reaction products, yield of single step reaction reaching above 90%, the total yield of vismodegib above 59% and the purity of vismodegib of more than 99.5%; at the same time, the invention has mild reaction conditions and easy posttreatment, and is suitable for industrial production.